Nonlinear Hydrophysical Disturbance Infragravity Sea Waves - Stanislav Dolgikh; Sergey Budrin; Efim Pelinovsky; Valery Antonov (Geosciences)
An analysis of the behavior of the infra-gravitational sea wave revealed nonlinear hydrophysical disturbance of the “rogue waves” type. This disturbance is associated with transformation of sea waves when they move along a coastal marine area of decreasing depth, and with interaction with wind waves. These conclusions are confirmed through analysis of in situ data of the laser interference pressure meter of the hydrosphere in this paper and previous works. Full-scale data were obtained on the shelf of the Sea of Japan. During processing of in situ data, we focused on sea waves with periods ranging from 1 to 10 min.